PENGARUH DRILL TRAINING DENGAN MEDIA BOLA GANTUNG TERHADAP KEMAMPUAN SMASH KEDENG SEPAK TAKRAW - Bastia, Bastia; Atiq, Ahmad; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe reseach problem in this rpspach is the low ability to smash kedeng extracurricular soccer takraw athletes SMP Negeri 21 Pontianak. This respach  to purpos the effect of drill training using the hanging ball media on the smash ability of kedeng sepak takraw soccer takraw extracurricular athletes at SMP Negeri 21 Pontianak City. The research method used in this research is experiment. The form of experimental design use One Group Pretest-Posttest. Sampling use a purposive sampling technique, namely 21 students from Pontianak City Junior High School who participated in extracurricular activities totaling 20 students. Data analysis was performed by t-test analysis, but before the t-test the normality and homogeneity tests were first performed. The results of the study are Thitung> Ttabel (4.19> 2,093). From tha drill we can see an increase the studnk ability about 2.6034 which catagorized strong effect,tis indicatil there is a significan result on the drill training method using the hanging ball media on the kedeng sepak takraw smash ability. Smash results after being treated (treatment), in the mean posttest is greater than the mean pretest (16.45> 7.45). It Means the results of the kedeng sepak takraw smash ability on extracurricular students of SMP Negeri 21 Pontianak City have increased. Therefore, drill training using hanging ball media can be applied to kedeng sepak takraw smash practice. Keywords: Drill Training, Hanging Ball Media, Smash kedeng